The Effecct of cisplatin on male white mice testicular tissue - Dick Moch. Rizal Dick Moch. Rizal (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2008)
Background: Cisplatin is a potent anticancer drug. In the therapy of various kinds of tumours. such as testicular, ovarian, bladder and lung cancer, cisplatin is used. It has cytotoxic and antimitotic effect on cell and tissue. Some studies reported the negative effect of cisplatin on male reproductive system.Objective: To know the effect of cisplatin on testicular tissue of male white miceMethods: Ten male white mice of DDI strain, 2 months old, 28.8-33.0 grams were classified into control group (5 mice) and treatment group (5 mice). The animal models were given standard feeding LPPOM, while those the control group were given CMC-Na 0.5% orally for 7 days. Cisplatin was given to the treatment group intravenously in the dose of 3 mg/kgBW for 7 days. At the end of the experiment, the animal model was killed by decapitation and the testicle was taken out. The testicle was placed in 10% formalin solution and processed for histology preparation with hematoxilin (Meyer) eosinand analyzed under binocular microscope.Results: All mice in the treatment group showed mild to severely damaged testis. There were serious spermatogenic and Sertoli cell disruption in severely damage testis.Conclusion: Intravenous injection of 3 mg/kgBW cisplatin for 7 days had deleterious effects on testicular tissue of male white mice, resulting in mild to severe damage.Key words: cisplatin - spermatogenesis - tubulus seminiferous - testicular damage